Resident-Memory T Cells in Tissue-Restricted Immune Responses: For Better or Worse? - Steinbach, Karin; Vincenti, Ilena; Merkler, Doron (Frontiers in Immunology, 2018)
Tissue-resident-memory CD8+ T cells (TRM) have been described as a non-circulating memory T cell subset that persists at sites of previous infection. While TRM in all non-lymphoid organs probably share a core signature differentiation pathway, certain aspects of their maintenance and effector functions may vary. It is well established that TRM provide long-lived protective immunity through immediate effector function and accelerated recruitment of circulating immune cells. Besides immune defense against pathogens, other immunological roles of TRM are less well studied. Likewise, evidence of a putative detrimental role of TRM for inflammatory diseases is only beginning to emerge. In this review, we discuss the protective and harmful role of TRM in organ-specific immunity and immunopathology as well as prospective implications for immunomodulatory therapy.